Poverty, Educational Failure and the Child-Labour Trap: The Indian Experience. (April 2015) - Sasmal, Joydeb; Guillen, Jorge
Poverty is considered to be the most important cause of child labour and it deprives children of schooling and acquiring human skill. The poor children grow as unskilled workers and earn low wages in adulthood. So, poverty persists and the parents are forced to send their children to work and a child-labour trap is formed. The econometric analysis using state level panel data in the Indian context demonstrates that poverty, illiteracy and child labour are significantly correlated. The results show that poverty adversely affects children's schooling and education and results in persistence of poverty thereby creating a child-labour trap.